A Study on the Selection of Co? Source Scenarios for the Implementation of a Ccus-Eor Pilot Project Using the AHP-Topsis Method at Field-X - Fridam Amruloh Baqarizky; Wawan Aries Widodo (International Journal Labs, 2026)
Carbon Capture, Utilization, and Storage–Enhanced Oil Recovery (CCUS–EOR) is a strategic approach to increasing crude oil production while supporting carbon emission reduction efforts in the oil and gas industry. This research aimed to determine the most suitable CO? source scenario for the CCUS–EOR pilot project in Field X using the AHP and TOPSIS methods and to evaluate its technical and economic feasibility. AHP was applied to determine the weights of four main criteria: CO? quality and specifications, CO? reservoir and supply capacity, distance and transportation requirements, and operational risks. TOPSIS was then used to rank alternative CO? sources, and the results were validated through technical and economic evaluations. CO? quality and specifications emerged as the most dominant criterion, with a weight of 55.8%. Technically, the implementation of CCUS–EOR was considered feasible with the addition of supporting facilities, including compression systems, dehydration units, booster compressors, and pumping systems. The projected CO? injection capacity reached 106,966 tCO? per year and was estimated to increase oil production by 146,000 barrels per year. Economically, the project generated annual revenue of approximately USD 11.62 million, with a capital expenditure (CAPEX) of USD 12.63 million, annual operating expenditure (OPEX) of USD 1.77 million, and cumulative discounted cash flow of USD 4.45 million at the end of the second year. The project achieved an internal rate of return (IRR) of 35.5%, a discounted payback period of 1.45 years, and a net levelized cost of CO? (net LCO?) of ?USD 27.6. The results demonstrated that the CCUS–EOR pilot project was technically and economically feasible, with the potential to increase oil production, reduce carbon emissions, and minimize dependence on routine flaring.